SISTEM INFORMASI SERVICE MOBIL DI PT. DUNIA BARUSA - Kurniawan, Zefri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2021)
The research objectives are; 1) To find out the Information System for Car Service Data Input PT. Dunia Barusa Banda Aceh City, 2) Designing Information System for Car Service Data Input PT. Dunia Barusa Kota Banda Aceh is web-based, and 3) Exploring the needs of users of the Car Service information system at PT. Barusa World Banda Aceh City. Broadly speaking, this research is divided into three stages, namely pre-development data collection, development and implementation, and post-development data collection. While in software development using a linear sequential model is often called the waterfall model. The results of the study can be concluded that; 1) The realization of this car service information system makes it easier for the sales department to provide information to customers about the availability of goods without having to check the warehouse, 2) With this system, car sales and maintenance services are easier because it can be done in only one part, namely the service section, 3) Make it easier for leaders to obtain various kinds of reports related to the sales process, car maintenance because all reports are available in this service information system, and 4) Help leaders to make decisions related to adding employees, purchasing goods and other decisions from the reports generated by the system. can be obtained at any time.